2019
DOI: 10.1093/cid/ciz545
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin to Distinguish Viral From Bacterial Pneumonia: A Systematic Review and Meta-analysis

Abstract: Because of the diverse etiologies of community-acquired pneumonia (CAP) and the limitations of current diagnostic modalities, serum procalcitonin levels have been proposed as a novel tool to guide antibiotic therapy. Outcome data from procalcitonin-guided therapy trials have shown similar mortality, but the essential question is whether the sensitivity and specificity of procalcitonin levels enable the practitioner to distinguish bacterial pneumonia, which requires antibiotic therapy, from viral pneumonia, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
129
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(152 citation statements)
references
References 39 publications
11
129
1
11
Order By: Relevance
“…44 An elevated serum PCT is often found in patients with sepsis and septic shock. 39 While it is still controversial whether PCT can accurately distinguish bacterial or viral pneumonia, 45 it was found that PCT-guided therapy in acute respiratory infections reduces the antibiotic exposure and side effects, and improves the survival rate. 46 Bacterial infections trigger extrathyroidal synthesis of PCT, which is actively maintained by elevated values of IL-6, IL-1β, and TNF-α, while viral infections hinder PCT production due to interferon-γ.…”
Section: Discussionmentioning
confidence: 99%
“…44 An elevated serum PCT is often found in patients with sepsis and septic shock. 39 While it is still controversial whether PCT can accurately distinguish bacterial or viral pneumonia, 45 it was found that PCT-guided therapy in acute respiratory infections reduces the antibiotic exposure and side effects, and improves the survival rate. 46 Bacterial infections trigger extrathyroidal synthesis of PCT, which is actively maintained by elevated values of IL-6, IL-1β, and TNF-α, while viral infections hinder PCT production due to interferon-γ.…”
Section: Discussionmentioning
confidence: 99%
“…Procalcitonin, preferentially rising in bacterial infections, has demonstrated clinical utility in safely decreasing antibiotic use, though that finding was not reproduced in a recent, large, U.S.-based study [[5],[6]]. With respect to its ability to distinguish bacterial and viral etiologies, procalcitonin has shown only modest performance [7], [8], [9]. Biomarker panels that combine multiple analytes may impart greater sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…49 However, in a recent meta-analysis of 12 studies in 2408 patients with community-acquired pneumonia of known aetiology, the sensitivity and specificity of serum procalcitonin to differentiate between bacterial and non-bacterial pneumonia were both 55%. 50 This suggests that a procalcitonin level alone is unlikely to provide enough evidence to differentiate between a viral and a bacterial infection. Current guidance by the Infectious Diseases Society of America does not recommend using procalcitonin as part of clinical judgement.…”
Section: Altered Mentation (Glasgow Coma Scale <15)mentioning
confidence: 99%